Fear [videorecording (DVD)] - Khristov, Ivaĭlo, 1955-; Yancheva, Svetlana; Fleming, Michael (Actor); Yaneva, Kristina; Savov, Ivan, 1956-; Bochev, Stoyan (Film Movement series., 2022)
Svetla, a strong-willed widow, lives alone in a small Bulgarian village close to the Turkish border. She has recently lost her job as a teacher due to the lack of families with young children. One day, while hunting in a forest, she encounters an African refugee, Bamba, who is trying to reach Germany, and will bring about a dramatic turn in her life. Reluctantly, she offers him hospitality, but day after day, a bond develops as Bamba learns the language and takes part in her daily life.